Pengaruh Jumlah Uang Beredar terhadap Inflasi dan BI Rate serta Dampaknya terhadap Indeks LQ45 di Bursa Efek Indonesia (BEI) Periode 2010 2014 - Fathorrahman Fathorrahman; Imam Suaydi (BISMA (Bisnis dan Manajemen), 2018)
The capital market is an important instrument in the economy of a country, because the capital market also reflects the state of the country's economy. Capital market in Indonesia is the Indonesia Stock Exchange (IDX) based in the capital city, Jakarta. In the Indonesian stock exchange there are different classifications of stock indices, but the stock index movements are frequently used reference is LQ45. Many factors affect the movement of shares in the Indonesia Stock Exchange (IDX) especially LQ45, among others, the money supply, inflation and the BI Rate. On the other hand, the money supply also has an influence on inflation and BI Rate. The purpose of this study was to determine how the effect of the money supply directly against inflation and BI Rate, and how it impacts indirectly against LQ45 through inflation and BI Rate in Indonesia during the period 2010-2014. In this study, the population used is LQ45 and sample research is LQ45 period 2010-2014. Data analysis method used in this research is the analysis of the path (path analysis). In this study the data Inflation, BI Rate in the data each month during the study period of 2010 to 2014 on the website of Bank Indonesia (BI) (www.bi.go.id) and the data amount of money every month during the study period of 2010 to 2014 in Central Bureau of Statistics. The test results show the effect of which has been carried out during the study period (2010 - 2014) that the first structure money supply shows the influence of the (positive) is significant, in both structure money supply showed a positive effect (not significant), And the third structure shows that the money supply effect (positive) significant to LQ45, money supply no effect on inflation, money supply shows effect results (not significant) of the BI Rate. And for intervening results show that the variable inflation and BI rate can not be used as an intervening variable in the study